In vivo genotoxicity evaluation of a treated urban sewage sludge sample - Marzo Solano, Marize de Lourdes [UNESP]; Alves de Lima, Patricia Lepage [UNESP]; Lozano Luvizutto, Joao Francisco [UNESP]; Pereira Silva, Paula Regina [UNESP]; Umbuzeiro, Gisela de Aragao; Camargo, João Lauro Viana de [UNESP] (Elsevier B.V., 2009)
Tons of sludge is produced daily in sewage treatment plants of large cities, causing an enormous disposal problem. Because recycling has been proposed to mitigate the Situation, the potential adverse health effects of the sludge should be verified before that policy is undertaken. The present study is a part of an assessment of oral toxicity in rats fed with sewer-treated sludge and aimed to contribute to its genotoxicity characterization. After a 2-week acclimatization period, male and female Wistar rats were fed ad libitum for 90 days a pelleted commercial diet containing 0. 5000. 10,000 and 50,000 ppm of a treated sludge sample. The potential mutagenic or genotoxic effect was detected in recent animal cells by the bone marrow micronucleus test and the comet assay, respectively. For the comet assay peripheral blood samples were obtained immediately before the sacrifice from the periorbital plexus, Following sacrifices, polychromatic erythrocytes (PCEs) were analyzed in femoral bone marrow smears and the frequencies of micronucleated polychromatic erythrocytes (MNPCEs) were registered. Results of both assays indicated that exposure to any of the sludge concentrations tested did not increase the frequency of MNPCEs or the levels of DNA damage when compared to non-exposed concurrent control rats. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Sewage sludge; Urban sludge; Genotoxicity; Micronucleus test; Comet assay